The Early-Stage Development and Content Validity Examination of Ubaya Vocational Interest Inventory - Artiawati Artiawati; Ni Putu Adelia Kesumaningsari; Darmawan Muttaqin; Aniva Kartika; Krismasita Surya Putri; Maria Fransisca Tiara Paramita; Ady Putra; Felix Handani; Alexander Yohan (Universitas Ahmad Dahlan, 2023)
Vocational interest alignment is the key for job seekers to successfully undertake training programs. However, the assessment tool under the context of the vocational system has not been available, specifically in the Employment and Transmigration Agency of the East Java Provincial Government in Indonesia. Therefore, this research aimed to develop an online assessment to measure the vocational interest of job seekers. It generated theories and items for the Ubaya Vocational Interest Inventory (UVII) and tested the content validity. The process of developing the construct of the UVII was conducted by reviewing the descriptions of job training programs in East Java Province. The examination of content validity involved 10 panelists, and the data were analyzed by the coefficient Aiken V. Based on the categorization of all training program reviewed, the results showed that there were 20 categories of vocations encompassing 4 clusters of interests, which were services, agriculture, arts, and engineering. There were 10 items developed for each category of vocational interest. The content validity examination found that 152, 32, and 16 items at 76%, 16%, and 8% were good (V>0.70), fairly good (V = 0.50 – 0.69), and poor (V<0.50), respectively. The findings indicated that most of the developed items represented the constructs measured. However, items in the fairly good category need to be revised, and those in the poor category should be changed with the new items.